Praeruptorin A reduces metastasis of human hepatocellular carcinoma cells by targeting ERK/MMP1 signaling pathway. Issue 4 (23rd November 2020) - Yu, Chen‐Lin; Yu, Yung‐Luen; Yang, Shun‐Fa; Hsu, Chung‐En; Lin, Chia‐Liang; Hsieh, Yi‐Hsien; Chiou, Hui‐Ling
Abstract: Praeruptorin A (PA) is one of the active ingredients found in the dried root of Peucedanum praeruptorum Dunn, has been reported to possess anticancer effects against various types of cancer. However, the effect of PA on human hepatocellular carcinoma (HCC) remains uncleared. In this study, our results indicated that PA did not induce cytotoxicity or alter cell cycle distribution in human HCC cells (Huh‐7, SK‐Hep‐1, and PLC/PRF/5 cells). Instead, PA inhibited the migration and invasion of human HCC cells while downregulating the expression of matrix metalloproteinase‐1 (MMP1) and activating the extracellular signal‐regulated kinase (ERK) signaling pathways. Furthermore, blocking the ERK signaling pathway through siERK restored the expression of MMP1 and the invasive ability of PA‐treated HCC cells. In conclusion, our results demonstrate the antimetastatic activity of PA against human HCC cells, supporting its potential as a therapeutic agent of HCC treatments.